Litigation against dermatosurgeons and cosmetologists and consumer protection act - Neerja Puri; Ashutosh Talwar (Our Dermatology Online, 2013)
The concept of beauty has acquired new dimensions due to the increasing awareness in general public about the aesthetic procedures. The problems between the patient and the cosmetologists arise when the patients expectations become very high and unrealistic. The classical concept of doctor - patient relationship born in the golden days of family physicians has undergone drastic change due to dramatic advancement in medical technology, availability of sophisticated imaging system, high tech electronics and preponderance of new diseases. However, the accountability of the doctors under the law of professional negligence has emerged as a debatable issue among the medical fraternity all over the country after the enactment of the consumer protection act, 1986, which has not only changed the law of medical negligence1, but created an inexpensive and speedy remedy against medical malpractice.